2016
DOI: 10.3390/atmos7040054
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Particle Matters and Hazardous Volatile Organic Compounds in Selected Hot Spring Hotels in Guangdong, China

Abstract: Abstract:In Guangdong province, many hot springs were exploited and developed into popular places for tourist. In addition, hotels have been set up near hot spring sites to attract people, including local citizens, to spend their spare time inside these so-called "spring hotels". In our study, indoor air quality was investigated in four hot spring hotels in Guangdong province, China. Measured indoor pollutants included CO 2 , CO, PM 10 , PM 2.5 and Volatile Organic Compounds (VOCs). As the result show, high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
(65 reference statements)
4
11
0
Order By: Relevance
“…However, they did not quantify the indoor PM increase as a result of room cleaning. In rural China where hot spring hotels were located, He et al (2016) examined indoor PM in the hotel rooms where hot spring water containing radon (Rn) was supplied and exhibited that indoor PM in their sampled rooms was higher than that of outdoor. They observed that indoor PM rose rapidly when occupants entered a room, slowly dropped after the occupants went to sleep and then rose again when they got up.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not quantify the indoor PM increase as a result of room cleaning. In rural China where hot spring hotels were located, He et al (2016) examined indoor PM in the hotel rooms where hot spring water containing radon (Rn) was supplied and exhibited that indoor PM in their sampled rooms was higher than that of outdoor. They observed that indoor PM rose rapidly when occupants entered a room, slowly dropped after the occupants went to sleep and then rose again when they got up.…”
Section: Introductionmentioning
confidence: 99%
“…Though it was observed that October and November recorded maximum CO concentration values > 700 µgm -3 which were higher than the values estimated for December, the percentiles' distribution analysis clearly indicate that concentrations were more skewed to the higher values in December than the previous months. This can be attributed to the increased occurrence of calm conditions resulting in poor ventilation (He et al, 2016). It was observed that frequency distributions of wind speed and wind direction categories for October, November and December, 2013 were similar except that they recorded 35.8, 34.3 and 49.1% occurrence of calm condition respectively (Table 1).…”
Section: Ventilation Corridorsmentioning
confidence: 90%
“…Given the differences among studies, including the nature of sampling (eg, indoor vs personal samples), testing methods, and the target VOCs measured, 45 semi‐quantitative comparisons are most informative. Several studies conducted in industrial areas in China have reported high indoor BTEX and TTVOC levels (even though relatively few target VOCs were included) as well as high outdoor levels (averaging 420 µg/m 3 ) 22‐24 . In hostels in New Delhi, India, TTVOC levels (11 target compounds) averaged 120 µg/m 3 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Volatile organic compound levels in hotels have been reported in a few studies, 22‐24 but information regarding inhalation exposure of hotel workers is missing. This omission is important since personal measurements typically exceed levels measured using indoor or area sampling; in hotels, this may result due to housekeepers' close and direct contact with cleaning agents 25 .…”
Section: Introductionmentioning
confidence: 99%